Socioeconomic Wellbeing Amid The COVID-19 Crisis : Indonesia and Malaysia - Nurul Hilmiyah; Mira Munira; Dewi Tri Rahayu; Muhammad Hakimi Shafiai; Zulfa Emeliya Zein (Institute for Research and Community Empowerment (LPPM TAZKIA), 2022)
Massive and ongoing outbreaks of the corona virus have become a serious threat with a negative impact on the living standards and socio-economic well-being of the community. The objective of this study is to investigate the severe level of pandemic impact on both countries, Indonesia and Malaysia, and analyze the effectiveness of policy response, particularly on the economic stimulus to bring back socioeconomic well-being on the right track. This article employs content analysis as well as a comparative approach between two countries, Indonesia and Malaysia. Both mitigation plans from Indonesia and Malaysia have advantages and disadvantages to their economy and socioeconomic conditions. It is expected that this study contributes both theoretically and practically to the field of socioeconomic well-being in both countries. Keywords: Covid-19, Socioeconomic Wellbeing, Mitigation Policy, Malaysia, Indonesia